Assessment of a strain 19 brucellosis vaccination program in elk. (7th March 2017) - Maichak, Eric J.; Scurlock, Brandon M.; Cross, Paul C.; Rogerson, Jared D.; Edwards, William H.; Wise, Benjamin; Smith, Scott G.; Kreeger, Terry J.
ABSTRACT: Zoonotic diseases in wildlife present substantial challenges and risks to host populations, susceptible domestic livestock populations, and affected stakeholders. Brucellosis, a disease caused by the bacterium Brucella abortus, is endemic among elk ( Cervus canadensis ) attending winter feedgrounds and adjacent areas of western Wyoming, USA. To minimize transmission of brucellosis from elk to elk and elk to livestock, managers initiated a B. abortus strain 19 ballistic vaccination program in 1985. We used brucellosis prevalence (1971–2015) and reproductive outcome (2006–2015) data collected from female elk attending feedgrounds to assess efficacy of the strain 19 program while controlling for potentially confounding factors such as site and age. From our generalized linear models, we found that seroprevalence of brucellosis was 1) not lower following inception of vaccination; 2) not inversely associated with proportion of juveniles vaccinated over time; 3) not inversely associated with additional yearlings and adults vaccinated over time; and 4) associated more with feeding end‐date than proportion of juveniles vaccinated. Using vaginal implant transmitters in adult females that were seropositive for brucellosis, we found little effect of vaccination coverage at reducing reproductive failures (i.e., abortion or stillbirth). Because we found limited support for efficacy of the strain 19 program, we support research to develop an oral vaccine and suggest that continuing other spatio‐temporal management actions will be most effective to minimize transmission of brucellosis and reduce dependency of elk on supplemental winter feeding. © 2017 The Wildlife Society. Abstract : To potentially eliminate brucellosis (bacterial disease caused by Brucella abortus ) in elk attending supplemental winter feedgrounds in western Wyoming, USA, managers implemented a ballistic vaccination program from 1985 to 2015. We found limited support for efficacy of the program and suggest that continuing other spatio‐temporal management actions will be most effective to minimize transmission of brucellosis and reduce dependency of elk on supplemental winter feeding.